PERANCANGAN IKLAN WEB UNTUK RTH (RUANG TERBUKA HIJAU) TAMAN TABEBUYA DENGAN MENGGUNAKAN PARALLAX - Amanah, Nurul; Rachman, Anung (Institut Seni Indonesia Surakarta, 2022)
Tabebuya Park naturally works as a Green Open Space of the Jakarta area that are used by Jakartans to exercise and recreation. However, during the pandemic, the problem of the decreasing of its visitors due to the obligation to follow health protocol was inevitable. In addition, visitors who need exercise and recreation are having trouble in finding the right facilities and places. The design of this web ad uses the Design Sprint method by Jake Knapp which consists of six stages that have been detailed by Google Venture, i.e Understand, Define, Diverge, Decide, Prototype, and Validate. This Tabebuya Park web ad is designed with the aim of answering the customer’s needs using the Challenge Map analysis process in the form of How Might We and Four Step Sketch. The result of this design are two alternative Tabebuya Park web ads designed based on the customer’s needs with nature design and Parallax template from Google Web Designer to create suitable, interesting, informative and interactive ads.